Global Phenomena and Social Sciences An Interdisciplinary and Comparative Approach (Springer International Publishing, 2018)
This book offers new perspectives on global phenomena that play a major role in today's society and deeply shape the actions of individuals, organizations and nations. In a complex and rapidly changing environment, decision-makers need to gain a better understanding of global phenomena to adapt and to anticipate the evolution of the global context. The authors-ten renowned international scholars of anthropology, economics, law, management and political science-propose an interdisciplinary and comparative approach to social sciences. They analyse how international phenomena, such as globalisation or transnationalisation, transform the disciplines of social sciences from an epistemological standpoint. Explaining what 'global' means in difference disciplines, the authors analyse several global phenomena that characterise today's international environment such as the circulation of norms and ideas, the linkages between war and globalization, corporate governance, and the impact of multinational enterprises on sustainable development and poverty reduction. Providing examples of analytical disciplinary approaches and guidelines for decision-makers in a fast-changing global context this book will be useful to scholars and students of anthropology, economics, law, management and political science as well as practitioners in the private and public sectors. .